PRINCE2 AGILE PRACTICAL IMPLEMENTATION GUIDE - STEP-BY-STEP ADVICE FOR EVERY PROJECT TYPE, SECOND EDITION - COOKE, JAMIE LYNN (IT GOVERNANCE LTD, 2021)
The PRINCE2 Agile® Practical Implementation Guide - Step-by-step advice for every project type, Second edition is an official AXELOS-licensed guide that explains the PRINCE2 Agile framework in clear business language with practical guidance on how to implement this framework for any project in your organisation.
Keywords: PRINCE2 (Project management); Project management.; elektronické knihy; electronic books